The application of DTM in highway design (IBM PC) /Mohd Wazir K. Othman - K. Othman, Mohd Wazir (1987)
Digital Terrain Model (DTM) have found numerous application in many field. However, we shall restrict ourselves here to two main subjects, considering photogranmetric data acquisiition techniques and civil engineering applications.